Group Theory Approach to Computer Translation of Medical German - Moore, G. W.; Riede, U. N.; Polacsek, R. A.; Miller, R. E.; Hutchins, G. M. (Methods of Information in Medicine, 1986)
Computer translators have been studied for almost four decades, but recent advances in speed and storage capabilities have made such translators accessible to small computer users. We obtained the computer typesetting file for a German language medical textbook and wrote computer software sufficient to obtain a draft quality English language translation of the entire book, at a speed of 9,671 words per hour. This translator uses two external tables, namely a word and idiom list and a list of grammatical rules, which completely specify the behavior of the translator. The grammatical rule table satisfies the properties of a mathematical group, and the inverse operation for this group allows one in principle to convert this German to English translator into an English to German translator. For the larger problem of creating multilingual computer translators, the group theory inversion property may allow one to substantially reduce the effort of creating a separate translator for each language pair. Future development of computer translators will depend upon the wider availability of computer-readable documents and will be aided by use of vocabulary and grammatical rule tables with group theory properties which permit the invertability between language pairs.
Keywords: Group Theory; Computer Translation; German Natural Language; Medical Translation